2007
DOI: 10.1540/jsmr.43.117
|View full text |Cite
|
Sign up to set email alerts
|

Vascular biology in sepsis: pathophysiological and therapeutic significance of vascular dysfunction

Abstract: Sepsis is the leading cause of mortality in critically ill patients. In this pathological syndrome, septic shock and sequential multiple organ failure correlate with poor outcome. The pathophysiology of sepsis with acute organ dysfunction involves a highly complex, integrated response that includes activation of number of cell types, inflammatory mediators, and the hemostatic system. Central to this process may be alterations in vascular functions. This review article provides a growing body of evidence for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 144 publications
1
81
0
2
Order By: Relevance
“…NO is a well-known vasoactive mediator which regulates vascular tone, platelet aggregation, coagulation, fibrinolysis and leukocyte activation (25). Release of NO from vascular endothelium may be influenced by wall shear stress, intravascular stasis and ischemia-reperfusion injury (26,27). In a previous study, plasma nitrate concentration was found to be significantly higher 5 min after reperfusion, compared to concentrations prior to ischemia (28).…”
Section: Discussionmentioning
confidence: 99%
“…NO is a well-known vasoactive mediator which regulates vascular tone, platelet aggregation, coagulation, fibrinolysis and leukocyte activation (25). Release of NO from vascular endothelium may be influenced by wall shear stress, intravascular stasis and ischemia-reperfusion injury (26,27). In a previous study, plasma nitrate concentration was found to be significantly higher 5 min after reperfusion, compared to concentrations prior to ischemia (28).…”
Section: Discussionmentioning
confidence: 99%
“…The nature of sepsis is an uncontrolled inflammatory response, of which the pathophysiological process is complicated involving a series of overall responses, including various cell factors, inflammatory mediators, and activation of the blood coagulation system, while the central link in this process is a change in the function of vascular endothelial (VE) cells (Gerszten et al, 1999). Sepsis, as the first line of defense, involves activation of VE cells, which subsequently release many inflammatory factors and adhesion molecules that mediate the migration of inflammatory cells from blood vessels to the sight of inflammatory injuries, where they bind to the infectious site and are activated by tyrosine phosphorylation of a series of plasmosins, which accentuates the inflammatory effects and can cause multiple organ failure (Matsuda and Hattori, 2007). The primary phenomenon in this process is the attachment of the hyaline leukocytes to the VE cells; various kinds of adhesion molecules and chemotactic factors are able to coordinate the transfer, adhesion, and accumulation of hyaline leukocytes to the endothelium, which finally destroys the endothelial cells to increase their permeability.…”
Section: Introductionmentioning
confidence: 99%
“…This pressure is developed by the number of oncotically active particles (principally proteins) unable to pass across the capillary wall which functions as a semi-permeable membrane separating these two compartments. Additionally, some fluid and small proteins including albumin are reclaimed by interstitial lymphatic transport instead of directly re-entering the vascular space [74]. Increases in interstitial water and solute volume occur when the normal balance of Starling forces is perturbed.…”
Section: Capillary Leakmentioning
confidence: 99%